The Real-Time Automated Monitoring System for Lateral Deflection of Underground Structures - Hang Chen; Huqing Liang; Mengxiong Tang; Sheng Jiang; Hesong Hu (Advances in Civil Engineering)
The lateral wall deflection is the most intuitive parameter to reveal the stability and safety of underground excavations. The existing automated approaches, such as to serialize dozens of inclinometers along casing pipes, are too expensive to be applied in most common projects. To guarantee stable automation and lower the costs, a novel system based on strain measurement is proposed in this paper to achieve real-time automated monitoring of underground excavations. The specially designed components are highlighted to benefit the mass industrial production and rapid in situ assembly. By theoretical comparisons, the accuracy and resolution performance of the proposed strategy are demonstrated to be better than those of the traditional manual method. The applicability of the mentioned system was verified by an engineering case, from which it was demonstrated that the proposed system works well to predict the lateral wall deflection of underground excavations. The sensitivity of the monitored results to the boundary conditions is also carefully discussed. The designed system has broad application prospects to provide timely data for safety assessment to prevent the unexpected failure of underground excavation as well as other engineering structures with dangerous lateral deflection or movement.